Mai i te Kāhui Mounga ki Te Toka Tūmoana : Māori social workers’ experiences of growing up, the influence of whānau on their upbringing, and how these experiences impact their social work practice : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy at Te Kunenga ki Pūrehuroa, Massey University, Manawatū, New Zealand - Watson, Andrea (Ange) Makere (Massey University, 2024)
Kaimahi (Māori social workers) are like toka tūmoana – sometimes standing steadfast in a sea of chaos and uncertainty when working alongside whānau on change journeys. This thesis examines kaimahi growing up experiences, the influence of whānau on their upbringing, and how these experiences impact on their mahi as social work practitioners. This qualitative research project utilised Kaupapa Māori theory, incorporating a Mātauranga-ā-Taranaki methodological approach. The pūrākau of Pukeonaki ki Taranaki was utilised to assist in the interpretation of kaimahi experiences resulting in the construction of an overarching Te Kāhui Mounga ki Te Toka Tūmoana framework. Sixteen kaimahi were interviewed for this project, alongside separate interviews for some of their whānau members – eleven individual whānau members participated in six whānau hui. Key findings identified that kaimahi bring their lived experiences to social work which enables them to connect with maginalised whānau they work alongside. Theoretical understandings about becoming within te ao Māori illustrate how social work practice is always evolving with no finite end. The research also captured the voices of the whānau of kaimahi who were positive about having social work trained whānau members, often accessing them for their specialist knowledge, skillset, networks and resources. Participants identified that Māori have always been social workers practicing kaimahi ā whānau within whānau, hapū and iwi. It is subsequently argued that contemporary Māori social work practice can be traced to the Parihaka peace resistance movement, as the first documented form of Māori social and community work in Aotearoa. He Whāriki Haumaru model, developed within this thesis, illustrates how natural social work happens within whānau Māori with the threads of aroha (loving relationships), mokopuna ora, ngā mātāpono ā whānau (whānau values and beliefs), te taiao, hāpaitia (whānau happiness, unity, and connection), pou manawa (resources and resilience) kōrero (clear communication), and moemoeā (whānau aspirations) included. Kaimahi ā whānau networks have always operationalised these Māori-centric value systems to encourage oranga-ā-whānau – flourishing families.
Keywords: Māori social work, Kaimahi, Kaimahi ā whanau, Oranga ā whānau, flourishing; Māori (New Zealand people); Services for; Minority social workers; Attitudes; Social workers; Education; New Zealand; Toko i te ora; Whānau; Tāngata whenua; Mana tangata; Māori Doctoral Thesis; 451126 Ngā mahi tauwhiro me te tika pāpori o te Māori (Māori social work and social justice)